Transición energética en Reino Unido para la integración de fuentes no convencionales de energía y redes inteligentes (2019)
This paper describes the UK's energy transition to achieve 25% renewable energy generation by 2016 and reduce per capita CO2 emissions from 10,744.1 kg CO2/pc in 1990 to 6,560.2 in 2016. But at the same time, studies are beginning to show that although the reform of the electricity market in the United Kingdom has taken a big step forward, it still faces serious challenges due to the reduction of support mechanisms for renewable energy and the political instability that this economy has had, and, therefore, investors have chosen to concentrate on managing their existing assets rather than planning for further growth.